Radiation enhanced reactivation of irradiated human adenovirus type 2 in human cells - Jeeves, Patrick William (My University, 1981)
Radiation-enhanced reactivation (ER) of a radiation-damaged mammalian virus is the term given to the observation that the survival of irradiated virus can be enhanced by irradiation of an appropriate host cell prior to infection. In this work, both UV enhanced reactivation (UVER) and gamma-ray-enhanced reactivation (γRER) of irradiated human adenovirus type 2 (Ad 2) were studied in a variety of normal and DNA repair-deficient human fibroblast host cell strains. In order to examine the lesion specificity of ER in human cells, experiments were performed using UV-irradiated and γ-irradiated virus. The investigation was carried out using a sensitive technique of indirect immunofluorescence, according to which irradiated and unirradiated cell cultures were infected with irradiated or unirradiated Ad 2 and were subsequently examined for the presence of viral structural antigens ('V' Ag) at a fixed time after infection.
In normal cells, γRER was found to operate on UV-irradiated as well as on γ-irradiated virus, and the efficiency of γRER for Ad 2 Vag was somewhat greater for γ-irradiated (E ~ 0.52) than for UV-irradiated (E ~ 0.39) virus. UVER was also found to operate on both UV-irradiated virus and γ-irradiated virus, although the efficiency of UVER for γ-irradiated virus (E ~ 0.18) was slightly less than that for UV-irradiated virus (E ~ 0.24). Although caffeine was found to inhibit both UVER and γRER in these cells under the conditions of the assay used, the results of time course experiments indicated that UVER and γRER operate via different mechanisms, at least in part.
Cockayne's syndrome (CS) fibroblasts, as well as excision repair-deficient Xeroderma pigmentosum (XP) fibroblasts from complementation groups A and D, were generally proficient in γRER of irradiated Ad 2, although there were intrinsic differences in the levels of γRER expressed in different cell strains. These strains also expressed UVER at levels comparable to those observed in normal fibroblasts, for UV-irradiated as well as for ϒ-irradiated virus. In these strains, however, the UVER profiles exhibited peaks whose positions were shifted to lower UV doses to the cells, relative to that for normal cells. Although the level of UVER for γ-irradiated virus was consistently lower than that for UV-irradiated virus in these cells, the peak UVER positions for UV-irradiated virus and γ-irradiated virus were very similar, if not identical, and these UV doses corresponded to approximately the same UV survival of the host cells themselves. Excision repair-proficient XP variant cells expressed only low levels of γRER and UVER, suggesting a possible role for cellular postreplication repair in the mechanism responsible for ER in human cells. An excision-deficient XP fibroblast strain belonging to complementation groupA, but derived from a patient afflicted with the severe De Sanctis-Cacchione form of XP, was found to express no γRER of UV-irradiated Ad 2, and was absolutely deficient in UVER of either UV-irradiated or γ-irradiated virus.
The results are discussed in terms of the hypersensitivity of CS and XP cells to certain DNA-damaging agents, their UV-hypermutability, as well as the DNA repair deficiencies known or thought to be harboured by these cells. Enhanced virus reactivation in mammalian cells is believed to be analogous to Weigle reactivation (WR) of irradiated phage in E. coli. WR is one of a number of so-called "SOS" functions which are induced in E.coli by various mutagens and which include error-prone repair of phage and bacterial DNA.
Keywords: Biology; Biology